Crítica da educação centrada nas competências socioemocionais - Magalhães Neto, Alberto Coelho de (2019)
The present research investigates, from the perspective of critical theory, elaborated mainly by Theodor W. Adorno, Max Horkheimer and Herbert Marcuse, and from the contributions of social psychology, especially from the researches reported by Henry Wallon and Lev Vygotsky: (a) the intention of the education proposal centered on socio-emotional competences, highlighting the definition of competences and social-emotional competences given by the promoters of such educational proposition: Organization for Economic Co-operation and Development (OECD) and Ayrton Senna Institute (IAS); and (b) the social and psychological bases presented in such proposal. It was verified that the aim sought by the teaching of socio-emotional competences is related to the ideology of technological rationality, in the way described by the critical theory. In addition, it can be verified that applied to education, these competences, are shown as technology used, through "psychology", to adapt the individual to the standards of contemporary society. It has been shown that in order to achieve this purpose, education is strategically employed to adapt, conform, obey and heteronomy the students, justified according to their proponents, on a social and psychological basis, which, in turn, omit relevant studies and researches of social psychology and pedagogy, precisely, because they go against those justifications, as such research shows the crucial influence that culture, society and language have on the process of character and personality development (VYGOTSKY and WALLON), added to the inseparability of cognitive and affective-emotional abilities (BLOOM et al., VYGOTSKY and WALLON)